Development and Validation of Mastery Concept Based Pre-Learning Questions to Support The Implementation of RADEC (ReadË—AnswerË—DiscussË—ExplainË—Create) Learning Model - Sumirat, Fanny; Sopandi, Wahyu; Nurhayeti, Yeti; Kusumastuti, Fransiska Astri; Restiana, Rendi; Sujana, Atep (PrimaryEdu : Journal of Primary Education, 2022)
The fact shows that elementary school students are generally passive because most of the elementary school teachers only ask lower-order cognitive questions such as memorization. Therefore, the purpose of this study was to develop pre-learning questions that are able to stimulate and equip students to have higher order thinking skills. This study was using a research method for developing and evaluating instruments by adapting the instrument development process that has been developed by DeVellis (2003). This development process took two phases, that was the development phase and the validation phase. Pre-learning questions are made up of a set of questions for the fourth grade of elementary school with a validated energy theme. Data analysis was carried out through validity testing uses the SPSS version 25. The test results of preË—learning questions show that the questions are feasible to use. The implication of this study is to produce a cognitive assessment instrument whose validity is tested in accordance with the appropriate cognitive stages to support the implementation of the RADEC (ReadË—AnswerË—DiscussË—ExplainË—Create) learning model used in schools by teachers.